2015
DOI: 10.5539/res.v7n2p49
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Basis of Higher Education Institution Competiveness Assessment

Abstract: The author's standpoint regarding the category definition of "higher education institution competitiveness" is given in the paper. The most important characteristic of the general higher education institution competitiveness is defined as satisfaction of internal stakeholders-employees, achieved by means of implementing two directions: meeting employees' needs in decent working conditions; meeting needs of external stakeholders to the fullest extent allowing personnel to be proud of belonging to a higher educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The systematic review carried out by Adamu et al (2017) concluded that macro-environmental factors such as social, scientific, technological, economic, political and legal aspects; micro-environmental factors such as students, business community and society (Ashmarina et al , 2015); and different types of relationships with society, firms, government, potential students and students’ power affect HEIs’ competitiveness (Mainardes et al , 2011) and consequently their efficiency.…”
Section: Influencers Of Higher Education Institutions Efficiency and ...mentioning
confidence: 99%
“…The systematic review carried out by Adamu et al (2017) concluded that macro-environmental factors such as social, scientific, technological, economic, political and legal aspects; micro-environmental factors such as students, business community and society (Ashmarina et al , 2015); and different types of relationships with society, firms, government, potential students and students’ power affect HEIs’ competitiveness (Mainardes et al , 2011) and consequently their efficiency.…”
Section: Influencers Of Higher Education Institutions Efficiency and ...mentioning
confidence: 99%
“…Being competitive means occupying a dominant or developing position in internal and external markets [7]. The competitiveness of higher education institutions characterizes the ability to meet the needs of internal and external stakeholders based on competitive advantage that is relevant to internal conditions and external conditions [8]. The internal environment of higher education institutions consists of: material, finance, personnel, infrastructure and other internal resources, and external factors formed by the external micro environment (students, and society as a whole) and the macro (external) environment influenced by national policies in the field social, political, economic, legal, scientific and technological factors [9].…”
Section: A Higher Education Competitivenessmentioning
confidence: 99%
“…At the lower programme level, actions to measure and improve the design, content and delivery of the study programmes are developed and undertaken (Roskosa and Stukalina, 2018). The quality of services at the programme level should be the ground for service quality improvement actions at the institution level since the quality management procedures of the programme should comply with the quality policy of the HEI (Roskosa and Stukalina, 2018;Suomi, 2014;Brewer and Zhao, 2010;Ashmarina et al, 2015) by assessing and enhancing the design, content and delivery of the study programmes (Hénard and Roseveare, 2012).…”
Section: Introductionmentioning
confidence: 99%